2012
DOI: 10.1097/fpc.0b013e3283588fe5
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 genotype affects age-related decline in flecainide clearance

Abstract: This study suggests that CYP2D6 genotype is a determinant factor of age-related decline in flecainide clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Although the metabolic function of CYP2D6 is reported not to decline by aging, other CYPs such as CYP1A2, CYP2C9, CYP2C19, and CYP3A4 do . This is important in 2 aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the metabolic function of CYP2D6 is reported not to decline by aging, other CYPs such as CYP1A2, CYP2C9, CYP2C19, and CYP3A4 do . This is important in 2 aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the metabolic function of CYP2D6 is reported not to decline by aging, other CYPs such as CYP1A2, CYP2C9, CYP2C19, and CYP3A4 do. [36][37][38] This is important in 2 aspects. Firstly, metoprolol is mainly metabolized by CYP2D6 and secondarily metabolized by CYP3A4.…”
Section: Discussionmentioning
confidence: 99%
“…Another Asian-specific genetic factor affecting flecainide efficacy is CYP2D6*10, a polymorphism in the gene encoding the main metabolic enzyme for flecainide. Since about 60% of Japanese patients were reported to be CYP2D6*10 carriers [29], this variant as well as the SCN5A promoter HapB may result in a lower flecainide dose requirement in this population [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Age CYP2D6 seems to be functional already in first 2 weeks after birth [85][86][87] and seems generally not to decline substantially with older age; however, definite information is relatively sparse [88,89]. The article by Doki et al [89] found an interesting dependence of the age-related decline in flecainide clearance from the CYP2D6 genotype.…”
Section: Pregnancymentioning
confidence: 96%
“…The article by Doki et al [89] found an interesting dependence of the age-related decline in flecainide clearance from the CYP2D6 genotype. The age-related decline was 28.9% in IMs/PMs but only 6.1% in homozygote EMs.…”
Section: Pregnancymentioning
confidence: 96%